Specialist in Procurement as the Owner of the Public Procurement Process - Aleksey Evgenevich Kuzmin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article proposes recommendations on how to organize the procurement process for state and municipal customers based on the Deming-Schuhart principle (the PDCA cycle). The authors give the results of the first stage of the study of procurement practices of customers and propose the introduction of principles of project management in the public sector in the procurement practice of customers.